Regeneração tendínea em modelo murino: estudo da plasticidade central e investigação do efeito da modulação nitrérgica na plasticidade periférica - MORAES, Suellen Alessandra Soares de (Universidade Federal do Pará, 2017)
Tendon injuries cause strong impact on people due to pain and functional limitation resulting therefrom. After injury, the tissue starts to present a network of nerves. Furthermore, there is evidence for the occurrence of central plasticity after injury. Among the molecular factors involved in injury repair, nitric oxide (NO) is implicated in tissue remodeling, but its effects are not yet well understood. The purpose of this study is to ascertain the existence of central plasticity and the influence of NO in peripheral plasticity, functional limitation and tendon regeneration in murine model. To study the effects of NO in peripheral plasticity, we used control animals (CTRL, without injury) or animals treated with saline (SAL, 0.9% NaCl), L-nitro-arginine-methyl-ester (L-NAME, NO-synthesis inhibitor) and sodium nitroprusside (SNP, NO donor) every other day until the 21st day post injury (DPI). To evaluate central plasticity (L5 segment), an injury was performed alone and the spinal cord collected at 2 or 21 DPI. We analyzed the integrity and tissue organization in tendon samples by H&E, transmission electron microscopy and immunofluorescence, which was also used to evaluate peripheral plasticity. To assess tendon functional recovery, we determined the Achilles functional index, the joint angle and the open field. In spinal cord studies, we investigated glial reactivity and neuron involvement after injury by co-localizations with the cell activation indicator c-Fos. The findings of this research show that NO inhibition promotes tissue organization in association to an increase in collagen synthesis, secretion and deposition. Besides, L-NAME local administration seems to favor cell differentiation to tenocyte-like morphological types and improve the organization of nerve branches in between the collagen mesh in correlation with functional recovery at 21 DPI. On the other hand, increased levels of NO by SNP promoted worsening in almost all parameters analyzed. Our data also show tendon injury triggers a central plasticity process with an increase in glial reactivity at 2 DPI and ipsilateral cell activation at 2 and 21 DPI. Afterall, our findings point out occurrence of central plasticity after tendon injury and favoring of tissue repair and peripheral plasticity through nitrergic blockage, unraveling fundamental aspects of tissue recovery that may represent new targets for a therapeutical approach in tendon injuries.